DISPUTES IN MARRIAGE: POSSIBLE CAUSES AND SOLUTIONS IN THE CONTEXT OF INDIAN CULTURE - Kumari, Sandhya; Kusum Kumari; Mishra, Vidisha; Priyadarshini, Shweta; Renu Kumari; Sangeeta Rani; Kumari Deepmala (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Conflict in marriage is a widespread and important issue in Indian society. It is not only a matter between two individuals but affects two families and sometimes the entire community. The aim of this research paper is to analyse the possible causes of conflict in marriage and identify their solutions in the context of Indian culture. Through data survey, literature review and cultural analysis, we will try to understand why marital conflicts occur in Indian society and how they can be reduced. Our effort points to lack of communication and financial problems as the main causes of marital conflict, along with cultural differences, family pressure, personal dissatisfaction. Through this research, we conclude that communication, financial management and family counselling can be effective solutions.